Analysis of a Free-Space Optical Communication System - Kilinc Evran, Serap; Unverdi, N. Ozlem (IEEE, 2023)
In this study, the performance of a free-space optical (FSO) communication system in different weather conditions was analyzed. In FSO technology, which has an important place in communication technologies, the characteristics of the free-space channel used as a communication medium were investigated and the effects of weather conditions on communication were discussed. The system was modeled with the OptiSystem 7.0 simulation program. Obtained results were evaluated by eye diagram and maximum quality factor.
Keywords: Communication technologies; free-space optical communications; laser; amplifier; filter; Computer Science; Communication; Engineering; Telecommunications